ANALISIS POTENSI TERJADINYA FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE SPRINGATE (S-SCORE) PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Istiana, Siti (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to examine the potential for financial distress in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). By using the Springate (S-score) method to see how big the potential for financial distress that occurred before bankruptcy in the 2017-2020 period in food and beverage companies was. The method used in this study is a quantitative method with an associative approach. The data used in this research is secondary data and the data is collected through observation and literature study. The sampling technique used is purposive sampling technique by obtaining samples during 2017-2020. The data analysis methodology used is data analysis technique, classical assumption test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, hypothesis testing and coefficient of determination test (R2). Simultaneous test (F-count) obtained F-count value of 77.457 > F table 2.50. This value can be concluded that the ratio of working capital to total assets, the ratio of earnings before interest and taxes, the ratio of earnings before taxes to current debt and the ratio of sales to total assets have a significant effect on financial distress simultaneously. The coefficient of determination (R2) can be seen that the value of the determinant coefficient is 0.907, this shows that the dependent variable (financial distress) can simultaneously be explained by the dependent variable (that the ratio of working capital to total assets, the ratio of earnings before interest and taxes to total assets, the ratio profit before tax to current liabilities, ratio of sales to total assets) of 82.2%. During the observations, it was shown that the research data of 18 food and beverage companies listed on the Indonesia Stock Exchange were still in a state of financial distress.